Online multivariable process identification in the frequency domain. (6th July 2010) - Wang, Ya-Gang; Xu, Xiao-Ming; Cai, Wen-Jian
In this paper, a new technique for online multivariable process identification in the frequency domain is presented. Set-point changes in the control loops are performed so that the process frequency-response matrix is estimated with signal decomposition and frequency spectrum analysis method, and accurate transform-function matrix is identified as well. The required input and output data are obtained while the processes are still in normal closed-loop operation. Simulation example is given to show both effectiveness and practicality of the identification method for multivariable processes.